PERENCANAAN WAKTU PELAKSANAAN PROYEK DENGAN MEMPERTIMBANGKAN METODE PEMBAYARAN (STUDI KASUS: PROYEK HOTEL CITADINES BERAWA BEACH, BADUNG, BALI) - Astana, I Nyoman Yudha (Jurnal Ilmiah Teknik Sipil, 2022)
Project scheduling is an important part of project execution, which has the potential to become a problem for the failure of construction project execution time. Project scheduling has a direct effect on the cash flow of a project, especially the direct costs incurred. If the scheduling of project activities is not planned properly, it can cause a large negative cash flow, which can disrupt the running of the project. Therefore, it is necessary to conduct research on the planning of project activities by considering the payment method. This research was conducted at the Citadines Berawa Beach Hotel Project worth Rp.44,868,087,944, -., covering structural and architectural work, with a progress claim monthly payment system and a retention period of twelve months with an advance payment of 20%. This research uses the Microsoft Project 2019 application by entering a schedule of activities and implementation costs. Then a strategy is carried out to plan the project execution time so that it is optimal and results in an efficient use of funds. This strategy includes activities such as parsing the work duration, changing the lag time, changing non-critical path predecessors, changing the work start date, and splitting the execution of work items. From the scheduling model trial and error analysis conducted eleven times, the optimal implementation schedule is 300 days with no cash flow experiencing negative overdraft. Retention payments by the owner were made in the 37th week of the 3rd quarter of 2020, so the project profit was Rp3,859,237,349.